Cornelia de Lange syndrome and molecular implications of the cohesin complex: Abstracts from the 7th biennial scientific and educational symposium 2016. Issue 5 (12th February 2017) - Kline, Antonie D.; Krantz, Ian D.; Deardorff, Matthew A.; Shirahige, Katsuhiko; Dorsett, Dale; Gerton, Jennifer L.; Wu, Meng; Mehta, Devanshi; Mills, Jason A.; Carrico, Cheri S.; Noon, Sarah; Herrera, Pamela S.; et al.
Abstract : Cornelia de Lange Syndrome (CdLS) is due to mutations in the genes for the structural and regulatory proteins that make up the cohesin complex, and is considered a cohesinopathy disorder or, more recently, a transcriptomopathy. New phenotypes have been recognized in this expanding field. There are multiple clinical issues facing individuals with all forms of CdLS, particularly in the neurodevelopmental system, but also gastrointestinal, cardiac, and musculoskeletal. Aspects of developmental and cell biology have found common endpoints in the biology of the cohesin complex, with improved understanding of the mechanisms, easier diagnostic tests, and the possibility of potential therapeutics, all major clinical implications for the individual with CdLS. The following abstracts are the presentations from the 7th Cornelia de Lange Syndrome Scientific and Educational Symposium, June 22–23, 2016, in Orlando, FL, in conjunction with the Cornelia de Lange Syndrome Foundation National Meeting. In addition to the scientific and clinical discussions, there were talks related to practical aspects of behavior including autism, transitions, communication, access to medical care, and databases. At the end of the symposium, a panel was held, which included several parents, affected individuals and genetic counselors, and discussed the greatest challenges in life and how this information can assist in guiding future research. The Research Committee of the CdLS Foundation organizes this meeting, reviews, and accepts abstracts, and subsequently disseminates the information to the families through members of the Clinical Advisory Board and publications. AMA CME credits were provided by Greater Baltimore Medical Center, Baltimore, MD.